Ergonomic risks and physiological stress in mat-type paddy (Oryza sativa) seedling preparation - SHANKAR, SUBHAM; CHAUHAN, NARVENDRA SINGH; GUPTA, SAUMEN (The Indian Journal of Agricultural Sciences, 2026)
This study was carried out during 2023–24 at Ranipool, Gangtok, Sikkim to validate the physical characteristics, postural risks and physiological workload of farm workers engaged in manual mat-type paddy (Oryza sativa L.) seedling preparation. A total of 10 male workers (mean age: 34.1 ± 6.17 years, BMI: 22.72 ± 3.42 kg/m²) were analysed for their ergonomic risks and metabolic demands. Postural assessment using the Ovako Working Posture Analysis System (OWAS) and Rapid Entire Body Assessment (REBA). The results indicated that key activities such as soil placement, frame placement and broadcasting seeds posed "Very High Risk" (REBA score: 11.6–13.2) and required immediate corrective action. The physiological workload assessment revealed significant variations in oxygen consumption (VO₂: 9.70 ± 4.92 ml/min/kg), heart rate (HR: 102.20 ± 17.09 bpm) and energy expenditure (EE: 3.04 ± 1.54 kcal/min) across different phases of the task. ANOVA results confirmed that both worker differences and task phases significantly influenced workload, with heart rate responses increasing due to task repetition. The findings infer the need for ergonomic interventions, task re-design and improved workload management strategies to enhance worker safety and productivity.